A production of polyethersulfone asymmetric membranes using mixture of two solvents and lithium chloride as additive - Idris, Ani; Ahmed, Iqbal (Penerbit UTM Press, 2007)
Polyethersulfone (PES) asymmetric membranes were prepared by the wet / dry phase inversion process. Membrane dope formulation consisting of commercial-grade PES resin and a mixture of two different solvents dimethyleformamide (DMF) and commercial grade acetone with control ratio 3.47 was prepared. Tap water was used as the coagulant bath at room temperature. With a focus on the PES solvent mixtures DMF/acetone economical system, the effect of lithium chloride anhydrous (LiClH2O) as additive on the membrane’s performance was investigated. The performances of the PES membranes were evaluated in terms of various molecular weight PEG separation and permeation flux. Its molecular weight cut off is then determined. The PES membranes prepared from the two solvent mixture systems with LiClH2O additive possess excellent hydrophilic properties exhibited by the high permeation rates. Its solute rejection rates obtained were also superior compared to the membrane prepared from single solvent without LiClH2O additive.